If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5 = -2 Reorder the terms: 5 + -1x = -2 Solving 5 + -1x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = -2 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -2 + -5 -1x = -2 + -5 Combine like terms: -2 + -5 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 6x-11-3x=-7x-71 | | -5x-22=48 | | 2x+13=-14-7x | | 8x+5=-91 | | 7x+7=-56 | | 2z+9=14-3z | | 15-4y=-7y-3 | | 5+2z+9z=7z+41 | | 4y^2+4y+1+y^2=13 | | 4(5x-2)=7(2x+3) | | z^7-2z^4-2z=0 | | 2(x-5)=3x-18 | | 4(3b-1)+6=5(2b+4) | | 2x^3-11x^2+20x-12=0 | | 146=4i+42 | | 16=5(x-1)+1 | | 196=10h-474 | | 56-3x=15x+22 | | 9w-169=38 | | 16=2w-42 | | 12-9x=78-23x | | 2x-4(x+8)=3x+8 | | 6n+34=202 | | 6y-5(1-y)=5 | | 5x-4(x+8)=10x+8 | | 5x-4(x+9)=10x+24 | | 3=5x-67 | | 5x-4(x-8)=10x+24 | | 5x-4x(x-8)=10x+24 | | 3(2-x)=-14 | | 10x+12=762 | | 7-4y=6y-23 |